Engaging Buddhism why it matters to philosophy - Garfield, Jay L. 1955- (Oxford University Press, 2015)
This is a book for scholars of Western philosophy who wish to engage with Buddhist philosophy, or who simply want to extend their philosophical horizons. It is also a book for scholars of Buddhist studies who want to see how Buddhist theory articulates with contemporary philosophy. Engaging Buddhism: Why it Matters to Philosophy articulates the basic metaphysical framework common to Buddhist traditions. It then explores questions in metaphysics, the philosophy of mind, phenomenology, epistemology, the philosophy of language and ethics as they are raised and addressed in a variety of Asian Buddhist traditions. In each case the focus is on philosophical problems; in each case the connections between Buddhist and contemporary Western debates are addressed, as are the distinctive contributions that the Buddhist tradition can make to Western discussions. Engaging Buddhism is not an introduction to Buddhist philosophy, but an engagement with it, and an argument for the importance of that engagement. It does not pretend to comprehensiveness, but it does address a wide range of Buddhist traditions, emphasizing the heterogeneity and the richness of those traditions. The book concludes with methodological reflections on how to prosecute dialogue between Buddhist and Western traditions. Quelle: Klappentext.